The Eurozone crisis and the transformation of EU governance internal and external implications (Globalisation, Europe, multilateralism, 2016)
Research on European governance is central to understanding both the process of European integration and its external influence as a laboratory for multilateralism. This volume focuses on the impact of the recent Eurozone crisis and its far-reaching implications for European governance both inside and outside the EU borders.